Circulating PCSK9 levels are not associated with the conversion to type 2 diabetes. (January 2020) - Ramin-Mangata, Stéphane; Wargny, Matthieu; Pichelin, Matthieu; Le May, Cédric; Thédrez, Aurélie; Blanchard, Valentin; Nativel, Brice; Santos, Raul D.; Benseñor, Isabela M.; Lotufo, Paulo A.; Lambert, Gilles; Cariou, Bertrand
Abstract: Background and aims: PCSK9 is an endogenous inhibitor of the LDL receptor pathway. Recently, Mendelian randomization studies have raised a doubt about the diabetogenic risk of PCSK9 inhibitors. Here, we assessed the relationship between plasma PCSK9 levels and the risk of new onset diabetes (NOD). Methods: Fasting plasma PCSK9 levels were measured at baseline by ELISA in subjects without lipid lowering treatment in IT-DIAB (n = 233 patients with prediabetes, follow-up 5 years) and ELSA-Brasil (n = 1751; 27.5% with prediabetes, follow-up 4 years) prospective cohorts. The primary outcome in both studies was the incidence of NOD. The association of NOD with plasma PCSK9 levels was studied using multivariable Cox models. Results: Plasma PCSK9 levels were not significantly associated with NOD in IT-DIAB (HR (+1SD) 0.96, CI95% [0.76; 1.21]) and ELSA-Brasil (OR (+1SD) 1.13 [0.89; 1.42]). In ELSA-Brasil, a significant positive association between PCSK9 and worsening of glucose homeostasis, including the progression from normoglycemia to prediabetes, was found (OR (+1SD) 1.17 [1.04; 1.30], p  = 0.0074). Plasma PCSK9 concentration was also positively associated with the change in fasting plasma glucose between the first and second visit in ELSA-Brasil ( β  = 0.053, CI95% [0.006; 0.10], p  = 0.026). Plasma PCSK9 levels positively correlated with total cholesterol in IT-DIAB and ELSA-Brasil, but not with glucose homeostasis parameters, except for a positive correlation with HOMA-IR in ELSA-Brasil. Conclusions: Plasma PCSK9 levels were not significantly associated with NOD risk in longitudinal analyses. These data suggest that inhibition of the PCSK9 extra-cellular pathway should not be deleterious for glucose homeostasis. Graphical abstract: Image 1 Highlights: Like statins, PCSK9 inhibitors have been proposed to increase the risk of new onset diabetes (NOD). We show that PCSK9 levels do not predict the transition from prediabetes to NOD. Inhibiting circulating PCSK9 should be safe for glucose homeostasis.